Influence of growing conditions and seed of different qualities on yielding capacity and protein content in winter wheat grain - O. V. Onopriienko; M. I. Kulyk; A. O. Taranenko; S. V. Taranenko (Agrology, 2020)
The actuality of the research is determined by the solution of an important problem – the increase of the protein content in the grain of winter wheat on the basis of ecological difference of seeds quality and the conditions in which it was formed. The aim of the research is to establish the influence of plant growing conditions, ecological difference of seeds on yield, variability of protein content in grain and its output in winter wheat varieties of different origins. The research were performed in the Central Forest-Steppe of Ukraine with varieties of soft winter wheat Kubus and Chyhyrynka. Research methods: field experiment (study of the influence of growing conditions on grain protein content and its output, as well as on the level of yielding capacity), laboratory method (determination of protein content), correlation-regression analysis (determination of the relationship between experience factors), statistical method (to confirm significant difference between the investigated variants). According to the hydrothermal coefficient (HTC) the conditions of seed formation on the mother plants of winter wheat are determined: close to optimal, arid and moist. In accordance with the results of the first stage of research, it is determined that the grain yielding capacity was higher in the crops which were formed in the optimal and humid periods (from 4.4 to 4.9 t/ha). The influence of weather conditions of the period of formation and ripening of grain of winter wheat (Triticum aestivum L.) on the protein content and protein output was determined. Protein output is significantly higher (from 5.4 to 6.4 t/ha), in varieties whose seed formation occurred in optimal and arid conditions. The protein content in grains was higher (from 13.9 up to 14.0%) in offspring formed in arid conditions. At the second stage of works the dependence is established: sowing by the seeds grown in arid conditions allows receiving the offspring with the high content of protein, and vice versa. This is confirmed by a strong correlation for both winter wheat varieties tested (r = 0.59 for Chyhyrynka variety and r = 0.53 for Kubus variety). It is found that sowing with small seeds, formed in arid condition, significantly increases the protein content in the grain and protein output in the new crop. The influence of ecological difference of seed quality of winter wheat varieties of Ukrainian and foreign selection on the level of yielding capacity, protein content and its output in the grain of the obtained offspring was studied. The ways of leveling weather conditions on the protein content in grain on the basis of sowing of different fractions of seeds by size (mixture, large, middle and small seeds) formed in different growing conditions are established. The improvement of the ways of leveling weather conditions and their influence on the grain protein content on the basis of sowing a small fraction of seeds of winter wheat, formed in the arid growing conditions, with pre-sowing treatment by means of the biological preparations in the future is planned.